Penciptaan Nilai Berkelanjutan: Akuntansi Hijau, Modal Intelektual, dan Moderasi Strategis dalam Kinerja Perusahaan - Teti Rahmawati; Yayat Supriatna; Padli Muhammad Yusuf (Universitas Swadaya Gunung Jati, 2025)
This study aims to analyze the influence of green accounting and intellectual capital on company value with business strategy as a moderation variable. The research method used is a verifiable descriptive method. The study population is property and real estate sector companies listed on the Indonesia Stock Exchange for the 2018-2022 period. The sample used is 265 financial statements of 53 companies listed on the Indonesia Stock Exchange for the 2018-2022 period using probability sampling. The data collection technique uses the observation technique without participating while the data analysis technique with moderate regression analysis. The results show that business strategy moderates the influence of green accounting on company value, and business strategy moderates the influence of intellectual capital on company value. This research makes a major contribution to revealing the role of business strategy as a moderation variable that can strengthen the influence of green accounting and intellectual capital on company value, thus helping companies design more optimal strategies.